Cardiovascular response of students to physical exertion using the 'Trunk Flexion Test' - Iryna Ivanyshyn; Krzysztof Prusik; Daria Piatnytska; Victoriia Spuziak (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Multiple factors affect the health condition of students. In this regard, a key preventative measure is observing the students' level of physical preparedness. The aim of the study is to assess the cardiovascular system response of students to physical exercise using the 'Trunk Flexion Test'.